Proliferating Pilar Tumor of the Cheek Misdiagnosed as Squamous Cell Carcinoma - Se Il Lee; Joo Heon Choi; Kun Yong Sung; Joonhong Min; Hong Sil Joo (Wolters Kluwer Medknow Publications, 2022)
Proliferating pilar tumours, also known as trichilemmal tumours, are rare tumours that arise from the external root sheath of hair follicles. These lesions usually have a firm-to-soft texture and form small nodules, but may grow gradually, causing pressure ulceration or hyperkeratinisation. Because of this feature, care should be taken to differentiate proliferating pilar tumours from squamous cell carcinoma. An 89-year-old woman presented with a protruding horn-shaped mass on her left malar area, which was first misdiagnosed as squamous cell carcinoma and then revealed to be a low-grade malignant proliferating pilar tumour. We report this case due to its rarity and clinically atypical characteristics.